A Prospective, Split-Face, Randomized Study Comparing Picosecond to Q-Switched Nd: YAG Laser for Treatment of Epidermal and Dermal Pigmented Lesions in Asians - Chanida Ungaksornpairote (2020)
BACKGROUND: Whether picosecond lasers outperform Q-switched lasers in treating pigmented lesions has not been clearly evaluated. OBJECTIVE: To compare the efficacy and safety of picosecond and Q-switched lasers in treating epidermal and dermal pigmented lesions in Asians. METHODS: Eight subjects with lentigines and 6 subjects with acquired bilateral nevus of Ota-like macules were enrolled. Subjects was randomly treated with a picosecond laser on one side of the face and a Q-switched laser on the other side. Subjective assessments on pigment clearance, and adverse effect were obtained at Weeks 0, 4, 12, and 24 after the final treatment. RESULTS: Clinical improvement differed between the 2 laser systems at Week 4 (p = .034), Week 12 (p = .039), and Week 24 (p = .027), with 85.7% of picosecond and 57.2% of Q-switched laser sites showing >50% improvement at 6 months. There was no significant difference in the incidence of side effect and healing time, but picosecond laser was significantly associated with a lower treatment discomfort (p = .05). CONCLUSION: The picosecond laser seems to be more effective and better tolerated than Q-switched laser for the treatment of pigmented lesions in Asians.